Hypoxia driven by Caribbean Sargassum accumulation events - Jose Martinez Ortiz; Jenniffer Perez Perez; Roy A. Armstrong; Juan J. Cruz Motta; Travis A. Courtney (Royal Society Open Science)
Sargassum accumulation events threaten coastal ecosystems across the Caribbean and have been associated with severe hypoxia. However, our understanding of Sargassum-induced hypoxia is limited by the lack of continuous monitoring of seawater dissolved oxygen during Sargassum accumulation events and the absence of decaying Sargassum oxygen uptake rates. Here, we combined time series of dissolved oxygen with remote sensing of Sargassum areal coverage in early summer and late winter at Isla Magueyes, Puerto Rico. While mild/moderate hypoxia was more frequent in summer than in winter, severe hypoxia was only observed following two distinct Sargassum accumulation events in early and mid-September 2023. We conducted incubation experiments with fresh decaying Sargassum to quantify mean ± s.e. oxygen demand rates of 0.0038 ± 0.0005 mg DO d−1 mg Sargassum−1 and incorporated these rates into a box model to show that modelled night-time was more severe with increasing Sargassum biomass and that less biomass was required to reach severe hypoxia under warmer and longer residence time scenarios. Our results demonstrate that Sargassum accumulation can drive local hypoxia and that the frequency and severity of Sargassum-induced hypoxia events in the Caribbean will likely increase under ongoing warming. These findings could be leveraged for an early warning system for future Sargassum-induced hypoxia events.